Boosting hypochlorite’s disinfection power through pH modulation - Timir Baran Sil; Dmitry Malyshev; Marina Aspholm; Magnus Andersson (BMC Microbiology)
Abstract Purpose Hypochlorite-based formulations are widely used for surface disinfection. However, the efficacy of hypochlorite against spore-forming bacteria varies significantly in the literature. Although neutral or low pH hypochlorite solutions are effective sporicides due to the formation of hypochlorous acid (HOCl), their optimal conditions and the specific role of pH in disinfection remain unclear. These conditions also increase the solution’s corrosiveness and compromise its shelf life. Therefore, further research is needed to identify the pH conditions that balance solution stability and effective hypochlorite-based spore disinfection. Results This study investigates the impact of neutral to alkaline pH on the sporicidal efficiency of hypochlorite against a pathogenic Bacillus cereus strain. We apply a 5,000 ppm hypochlorite formulation for 10-min across a pH range of 7.0-12.0, simulating common surface decontamination practices. Our results demonstrate that hypochlorite is largely ineffective at pH levels above 11.0, showing less than 1-log reduction in spore viability. However, there is a significant increase in sporicidal efficiency between pH 11.0 and 9.5, with a 4-log reduction in viability. This pH level corresponds to 2 - 55 ppm of the HOCl ionic form of hypochlorite. Further reduction in pH slightly improves the disinfection efficacy. However, the shelf life of hypochlorite solution decreases exponentially below pH 8.5. To explore the pH-dependent efficacy of hypochlorite, Raman spectroscopy and fluorescence imaging were used to investigate the biochemical mechanisms of spore decontamination. Results showed that lower pH enhances spore permeability and promotes calcium dipicolinic acid (CaDPA) release from the core. Conclusion Our results highlight the complex relationship between pH, sporicidal efficacy of hypochlorite, and its shelf life. While lower pH enhances the sporicidal efficiency, it compromises the solution’s shelf life. A pH of 9.5 offers a balance, significantly improving shelf life compared to previously suggested pH ranges 7.0-8.0 while maintaining effective spore inactivation. Our findings challenge the common practice of diluting sodium hypochlorite with water to a 5,000 ppm solution, as this highly alkaline solution (pH of 11.9), is insufficient for eliminating B. cereus spores, even after a 10-min exposure. These findings are critical for improving disinfection practices, highlighting the importance of optimizing sodium hypochlorite effectiveness through pH adjustments before application.